Valuation framework for PCIERD-DOST intellectual property - Luching, Aileen N.; Imbang, Glen A.; Cruz, Edison D. (Quezon City University of the Philippines Diliman, 2010)
The Republic Act 10055 or the Philippine Technology Transfer Act of 2009 was enacted to address the technology transfer concerns of most research institutions in the country. According to the Philippine Council for Agriculture, Forestry and Natural Resources Research and Development (PCARRD), the country's technology transfer system is characterized by : lack of well-defined and unifying policy on technology transfer; insufficient investment in technology transfer and commercialization; weak private-public collaboration in R&D and commercialization; and lack of well-defined IP regimes in R&D institutions. The Implementing Rules and Regulations (IRR) of the law requires that guidelines on IP valuation, commercialization and information sharing should be developed to assist the science and research community in their endeavor to transfer promising technologies they developed. The Philippine Council for Industry and Energy Research and Development (PCIERD) experience on technology transfer started in 1999 when Moondish Foods Corp. (MFC) entered into a licensing agreement for the manufacture and marketing of Food and Nutrition Research Institute (FNRI) and PCIERD-developed technology-the "Canned Laing". Since it was their first time to license a technology, they agreed on a royalty rate of 3 percent of the gross sales, which they thought were fair to both parties. In the first few years of operation, MFC experienced losses and waived the payment of royalties. It was only in 2004, that MFC gained market acceptance and successfully penetrated the US, UK, Middle East and Canada markets. In 2008, MFC gain signed a technology transfer agreement (TTA) with FNRI and PCIERD to adopt another ethnic food product- the "Canned Pinakbet". The parties agreed for a 2 percent (of the gross sales) royalty, which is lower than the Canned laing rate. The MFC requested to lower the rate based on their experience when they first introduced the Canned Laing. The Council's licensing set-up shows that there is no available technology valuation system that will support its licensing activities. The lack of a valuation tool and information on the market and potential value of a technology sometimes delays and discourages the negotiation and licensing process. Furthermore, the potential value of a technology is not taken into consideration, hence this project. The project is on the adoption of a valuation model of the Ocean Tomo Intellectual Capital Equity to determine the value of two (2) PCIERD-assisted and monitored technologies-the "Microbial Rennet Technology" and the "Vitamin-rich Green Mango Juice". Ocean Tomo is the leading merchant bank based in Chicago and a well known IP valuation company in the U.S. The valuation model adopted is an "income approach" of valuation. It consists of five (5) main activities : Intellectual Property (IP) Identification, Assessment of Competitive Advantage, Market Quantification, Value Allocation and Risk Adjustments. The first phase of the project was identification of intellectual property (IP). Interviews with the technology developers and project monitors were conducted to gather information about the technology. Technology information was presented in the Technology Summary Form (TSF). The second phase was the conduct of technology assessment with the technical monitors and financial/marketing analyst to determine the readiness of technology for commercialization. The project made use of the existing Technology Assessment Protocol (TAP) of PCIERD and the Heslop et al Cloverleaf Model of Technology Transfer for the TEEPS scoring. The third phase focused is market quantification where the overall market, segmented market and the attackable market were determined based on industry data and market assumptions.
The fourth phase of the valuation process dealt with value allocation where royalty revenues were computed using several assumptions on the expected useful life of the technology, launch date, penetration rate, and ramp-up timeframe (time to reach maximum penetration). The last phase of the valuation was on risk adjustments where the royalty revenues were discounted with risk factors based on Razgaitis" Risk Adjusted Hurdle Rates (RAHR) to determine the net present value of the technology. Like any other activities involving the future, the technical risks, market risks, competitive risks and legal risks were taken into account in the conduct of valuation. Information generated from the process were presented in the valuation template developed. The template consists of the Cover, Valuation Summary, Technology Summary Form, Technology Assessment/Report, Target Market Profile, Valuation and Industry Study. The valuation template developed is recommended for use by PCIERD during licensing negotiations as it provides information about the technology, target market profile, market potential, industry performance and expected returns at different royalty rates. Though it has been established that the income approach to technology valuation is appropriate for PCIERD technologies, the challenge of integrating the activity in the technology transfer system of the Council as well as its capability to undertake the activity needs to be assessed. Given the fact that there is no exact formula for valuation, the Council should be aware that the resulting values are just near estimates of the potential value of the technology and still dependent on the assumptions and method used by the Valuators.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Department of Science and Technology (Philippines); Valuation .; Intellectual property